A Novel Photocathode Material for Sunlight‐Driven Overall Water Splitting: Solid Solution of ZnSe and Cu(In, Ga)Se2. (25th April 2016) - Kaneko, Hiroyuki; Minegishi, Tsutomu; Nakabayashi, Mamiko; Shibata, Naoya; Kuang, Yongbo; Yamada, Taro; Domen, Kazunari
Abstract : Thin films of a solid solution of ZnSe and CuIn0.7 Ga0.3 Se2 ((ZnSe) x (CIGS) 1–x ) are prepared by co‐evaporation. Structural characterization reveals that the ZnSe and CIGS form a solid solution with no phase separation. (ZnSe)0.85 (CIGS)0.15 ‐based photocathodes modified with Pt, Mo, Ti, and CdS exhibit a photocurrent of 7.1 mA cm −2 at 0 VRHE, and a relatively high onset potential of 0.89 VRHE under simulated sunlight. A two‐electrode cell containing a (ZnSe)0.85 (CIGS)0.15 photocathode and a BiVO4 ‐based photoanode has an initial solar‐to‐hydrogen conversion efficiency of 0.91%, which is one of the highest values reported for a photoanode–photocathode combination. Thus, (ZnSe)0.85 (CIGS)0.15 is a promising photocathode material for efficient photoelectrochemical water splitting. Abstract : (ZnSe)0.85 (CIGS)0.15 ‐based photocathodes for hydrogen evolution from water show a notably high onset potential of 0.89 VRHE under simulated sunlight. A photoelectrochemical cell composed of a (ZnSe)0.85 (CIGS)0.15 ‐based photocathode and a BiVO4 ‐based photoanode drives overall water splitting utilizing simulated sunlight without an external bias voltage, exhibiting a solar‐to‐hydrogen conversion efficiency of 0.91%.